2022
DOI: 10.2147/dmso.s379547
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Self-Care Activities During COVID-19 Lockdown in Patients with Type 2 Diabetes That Received a Comprehensive Care Program Training

Abstract: In 2020, several countries established a global emergency state. Lockdowns restricted people's lifestyles and daily activities to prevent coronavirus spread. These measures hindered diabetes mellitus control and lifestyle changes. This study aims to evaluate if attending a multidisciplinary program before the pandemic helped maintain a good metabolic state, lifestyle modifications, and mental health in patients with diabetes mellitus during the COVID-19 lockdown. Methods: Patients included in this study attend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…As a result, potentially, increases in weight with changes in diet and exercise, as well as reducing control over blood sugar levels, can occur, with non-diabetic individuals found to have an increased risk of T2DM due to weight gain because of lockdown measures [ 36 , 37 , 38 , 39 ]. However, this may not always be the case [ 38 , 40 , 41 , 42 , 43 , 44 ]. Having said this, various published studies have shown concerns with weight gain, the control of blood sugar levels, and potentially an increase in complications among patients with T2DM during the pandemic, which have been exacerbated by issues of compliance with prescribed medicines [ 36 , 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, potentially, increases in weight with changes in diet and exercise, as well as reducing control over blood sugar levels, can occur, with non-diabetic individuals found to have an increased risk of T2DM due to weight gain because of lockdown measures [ 36 , 37 , 38 , 39 ]. However, this may not always be the case [ 38 , 40 , 41 , 42 , 43 , 44 ]. Having said this, various published studies have shown concerns with weight gain, the control of blood sugar levels, and potentially an increase in complications among patients with T2DM during the pandemic, which have been exacerbated by issues of compliance with prescribed medicines [ 36 , 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%